Enhancing Learning Outcomes: Medical Students’ Perceptions of Effective Feedback in Problem-Based Learning - Tissa Octavira Permatasari; Catur Setiya Sulistiyana; Mellyna Iriyanti Sujana; Zalfa Azzura Zahira (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
Effective feedback is a critical component of Problem-Based Learning (PBL), particularly in medical education, as it enhances critical thinking, problem-solving skills, and academic performance. Despite its importance, student perceptions of feedback effectiveness in PBL remain diverse, with limited understanding of its impact on learning outcomes. This qualitative study employed a phenomenological approach to explore medical students' perceptions of feedback in PBL sessions at Universitas Swadaya Gunung Jati. A total of 234 students across first, second, and third-year levels were selected through stratified random sampling. Data were collected via open-ended questionnaires distributed through Google Forms and analyzed thematically to identify key themes. The analysis revealed three main themes: (1) Feedback Quality—students valued specific, clear, and evidence-based feedback over vague or general comments; (2) Timing of Feedback—immediate feedback post-PBL sessions was more effective compared to delayed feedback; and (3) Trust in Feedback Providers—students responded better to feedback from competent and trusted tutors. Constructive feedback improved motivation, confidence, and self-reflection, enabling students to address weaknesses and enhance performance. Effective feedback in PBL requires clarity, timeliness, and a strong relationship between students and tutors. Institutions should train tutors to deliver high-quality feedback and consider incorporating technology to provide timely and constructive feedback. This study offers insights for optimizing feedback practices in PBL to improve learning outcomes in medical education.